2016
DOI: 10.1167/iovs.16-19395
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Chick Choroids Exhibit Increased Retinaldehyde Dehydrogenase Activity During Recovery From Form Deprivation Induced Myopia

Abstract: PurposeIncreases in retinaldehyde dehydrogenase 2 (RALDH2) transcript in the chick choroid suggest that RALDH2 may be responsible for increases observed in all-trans-retinoic acid (atRA) synthesis during recovery from myopic defocus. The purpose of the present study was to examine RALDH2 protein expression, RALDH activity, and distribution of RALDH2 cells in control and recovering chick ocular tissues.MethodsMyopia was induced in White Leghorn chicks for 10 days, followed by up to 15 days of unrestricted visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…We and others 37,38,86 have previously shown that RALDH2 protein expression and RALDH enzymatic activity are detectible in the choroids of chick eyes, with negligible amounts in the retina/RPE and sclera. Moreover, ATRA synthesis is increased in the chick choroid during recovery from form-deprivation induced myopia, which results from an increase in RALDH2 protein expression.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…We and others 37,38,86 have previously shown that RALDH2 protein expression and RALDH enzymatic activity are detectible in the choroids of chick eyes, with negligible amounts in the retina/RPE and sclera. Moreover, ATRA synthesis is increased in the chick choroid during recovery from form-deprivation induced myopia, which results from an increase in RALDH2 protein expression.…”
Section: Resultsmentioning
confidence: 69%
“…We have previously established that RALDH2 expression and activity are increased significantly in recovering choroids 37 and that RALDH2 is responsible for elevated ATRA concentrations in recovering choroids. 38, 86 Moreover, when placed in vitro , only recovering choroids are capable of de novo ATRA synthesis. 37 The EC 50 value for inhibition of ATRA formation in living recovering choroids by compound 2 was estimated to be 119.7 nM, but DAR only inhibited a maximum of 51% of ATRA formation in recovering choroids (with maximum inhibition at 1 μM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations